2006
DOI: 10.1212/01.wnl.0000238518.34389.12
|View full text |Cite
|
Sign up to set email alerts
|

Creatine supplementation in Parkinson disease: A placebo-controlled randomized pilot trial

Abstract: Mitochondrial dysfunction plays a major role in the pathogenesis of Parkinson disease (PD). Creatine (Cr) is an ergogenic compound that exerts neuroprotective effects in animal models of PD. We conducted a 2-year placebo-controlled randomized clinical trial on the effect of Cr in 60 patients with PD. Cr improved patient mood and led to a smaller dose increase of dopaminergic therapy but had no effect on overall Unified Parkinson's Disease Rating Scale scores or dopamine transporter SPECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(119 citation statements)
references
References 10 publications
0
113
0
6
Order By: Relevance
“…91 Another blinded, placebocontrolled study of 2 g daily for 6 months then 4 g daily for 18 months in 31 PD patients compared with 17 placebo showed no significant differences compared with placebo. 92 An antiapoptotic agent, TCH346, did not demonstrate neuroprotection in early PD patients. 93 Rasagiline, a monoamine oxidase B inhibitor, has demonstrated benefit in a delayedstart study in early PD that may reflect modification of the progression of the disease over the period of study (18 months).…”
Section: Therapeutic Implicationsmentioning
confidence: 94%
“…91 Another blinded, placebocontrolled study of 2 g daily for 6 months then 4 g daily for 18 months in 31 PD patients compared with 17 placebo showed no significant differences compared with placebo. 92 An antiapoptotic agent, TCH346, did not demonstrate neuroprotection in early PD patients. 93 Rasagiline, a monoamine oxidase B inhibitor, has demonstrated benefit in a delayedstart study in early PD that may reflect modification of the progression of the disease over the period of study (18 months).…”
Section: Therapeutic Implicationsmentioning
confidence: 94%
“…Creatine also improved brain bioenergetics in a dose-ranging 31 P MRS study of adolescent females with drug-resistant depression (Kondo et al 2016). Yet, several clinical studies reported low-to-medium therapeutic potential of creatine to positively dysfunctional energy metabolism in Huntington's disease (Bender et al 2005) and Parkinson's disease (Bender et al 2006), also schizophrenia (Kaptsan et al 2007). Co-administration of creatine and ketogenic diet did not result in 31 P-MRS visible changes in muscle energy metabolism in patients with McArdle disease although the intervention showed some energy-independent beneficial effects (Vorgerd and Zange 2007).…”
Section: Tackling Impaired Bioenergeticsmentioning
confidence: 99%
“…88 Another placebo-controlled study evaluating creatine supplementation was conducted in 60 subjects. 89 This study differed from the NET-PD trial in that subjects were receiving levodopa and other anti-parkinsonian therapy (except for selegiline). The assessment of change over the 2-year study was made by comparing clinical ratings while subjects were receiving the same dosages of PD medications at the end of the study as were taken initially.…”
Section: Creatinementioning
confidence: 99%